Student Opinions on Psychomotor Learning Activities Used in Music Lessons - Soykunt, Neriman; Gorgoretti, Başak (Journal of History Culture and Art Research, 2021)
This study aims to determine the situation by examining the opinions of 8th-grade students about psycho-motor activities used within the scope of 8th-grade music lessons. Semi-structured interview technique was used as a qualitative method in the research. With this method, data were collected by conducting one-on-one interviews with 8th-grade students. The study was conducted with forty-four 8th-grade students. The obtained data were analyzed by making content analysis. According to the findings obtained from the interviews; It is understood that the psycho-motor activities used in schools are mostly similar, but there are problems in the implementation process, the activities cannot be used effectively and efficiently, and music lesson activities are not given enough importance due to the problems arising from the deficiencies in the material and learning environment. From the students' opinions, it is understood that the theoretical parts of the music lessons are long and the lessons conducted in this way are boring. Based on the students' opinions, it is understood that the singing activity is the most used psycho-motor activity, but this activity is not used to improve the musical knowledge and skills taught in the lessons, but to increase the students' interest in the lessons. It is understood that rhythm exercises, body percussion and instrument playing activities are less involved in music lessons than singing activities.